COMPARISON OF THE CONCEPT OF PANCASILA DELIBERATIONS AND CONSENSUS AND HABERMAS' THEORY OF COMMUNICATIVE ACTION IN DEMOCRATIC DISCOURSE: Perbandingan Konsep Musyawarah-Mufakat Pancasila dan Teori Tindakan ‎Komunikatif Habermas dalam Wacana Demokrasi - Aaisyah, Sitti; Fauzi, Muhammad Fahmi Basyhah (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2025)
Indonesia is a country whose government system is run with a democratic system. Pancasila, ‎which is the foundation of the state, contains the principle of democracy. The main principle of ‎the Pancasila-style democracy is deliberation to reach a consensus based on noble knowledge ‎and wisdom. This principle of deliberation is in line with Habermas's thesis of communicative ‎action but also has different implications. This paper compares the concept of deliberation-‎consensus ala Pancasila and Habermas's communicative action in implementing a democratic ‎system. This qualitative research analyzes data that includes historical literature, philosophy, and ‎scientific articles that discuss discourses related to Pancasila and Habermas's theory of ‎communicative action. The study results show differences in Eastern and Western culture in the ‎two discourses. In Pancasila deliberation and consensus, communal ties are very strong, while ‎the value of Western individualism in rationalizing a discourse becomes the color of Habermas' ‎theory.‎